A CASE SERIES OF ACUTE SYMPTOMATIC HYPONATREMIA DUE TO SIADH: AN UNUSUAL PRESENTATION OF COVID19 INFECTION - Devaraja, Vanusha; Raja Iskandar, Raja Yunalis; Hui, Foo Siew; Mohd Thabit, Alif Adlan (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The Syndrome of Inappropriate ADH Secretion (SIADH) is one of the most common causes of hyponatremia among medical inpatients. The evolution of SARS-COV-2 infection over recent years has led to atypical presentations, one being in the form of acute symptomatic hyponatremia secondary to isolated SIADH not associated with pneumonia. CASES We report a series of three unusual cases of Category 2 COVID-19 infection presenting with acute symptomatic hyponatremia secondary to SIADH. All three patients presented with symptoms of acute severe hyponatremia and coincidentally tested positive for SARS-CoV-2 virus without respiratory tract symptoms and normal chest imaging. All patients were fully vaccinated and boosted at least 3 months before the presentation. Clinical and biochemical workup confirmed SIADH in all three patients. They were treated with hypertonic saline in the initial phase, followed by fluid restriction as per recommendations. It was postulated that the inappropriate ADH secretion was mediated by increased inflammatory cytokines, especially interleukin 6 may be a direct effect of the SARS-CoV2 infection itself. CONCLUSION In the context of the ongoing COVID-19 pandemic, acute symptomatic hyponatremia without an obvious cause could be an atypical, isolated manifestation of SARS-CoV-2 infection. Awareness of these uncommon presentations is important so that specific treatment protocols or recommendations can be created and instituted to address this likely reversible but potentially fatal presentation of COVID-19.